Letters to TURBA: Letter from Tunis; Letter from Istanbul. Issue 2 (1st September 2022) - Safia, Selim Ben; in This Shit, I Am Not Alone
Abstract : Letter from Tunis: We will keep dancing … We just don't know quite yet how to keep on balance … In the aftermath of the Hors Lits Festival, I am writing to share with you the reality of artistic, and particularly choreographic, performance in Tunisia. Here in Tunis, we have to date only one national dance festival and two or three private festivals, still struggling for their existence. Faced with the lack of a strong event dedicated to dance, we conceived the Hors Lits Festival (literally, "out of bed"), offering performances within the privacy of spectator's homes: in a living room, a bedroom, or a kitchen … out of bed. This format has allowed us to reach a new audience, to present artists, to try out new artistic forms … to demonstrate the importance of creating alternative spaces for dance. Letter from Istanbul: There Is a Sonic Revolt in the Streets! When the government announced Turkey's withdrawal from the Istanbul Convention on 20 March 2021, we were waking up every day with the news of missing, murdered, raped, and beaten women and LGBTQ+ people. Our situation was sadly not unique; indeed, all around the world, our comrades had been struggling with the same systematic violence. Hence, we were not alone in this shit!